Engine performance and emission effects of diesel burns enriched by hydrogen on different engine loads - Karagoz, Y.; Sandalci, T.; Yuksek, L.; Dalkilic, A. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Although diesel engines will be used in future too, they are the indispensable part of our daily lives. However, steadily decreasing emission regulations limit values and cost increases due to corresponding need of hi-tech aftertreatment systems, and diesel fuels' increasing price in recent years force researchers to use alternative fuel types to use on diesel engines. In this work, hydrogen which is in gas phase is sprayed with gas injector from intake port and ignition is provided by diesel fuel coming from diesel injector. Sent hydrogen's energy content is stabilized at 30% in overall fuels and all tests committed are performed in 1100 rpm stable engine speed. Also, in different engine loads (40%, 60%, 75% and 100%) intake air enrichment with hydrogen effect on diesel engine's engine performance, emissions and effect on combustion have been examined. Obtained results show that in part load conditions enriched with hydrogen, NO emissions and soot emissions can be taken under control. However on, full load condition (100% engine load), with hydrogen addition, dramatical rise of NO emissions is observed. Working conditions with hydrogen + diesel fuel, it is obtained that engine load affects NO emissions significantly. On full load conditions, enriched with hydrogen, even though there is some rise in THC emissions, there are progresses in CO2 and CO emissions. Besides, peak in-cylinder gas pressure and peak heat release rate have risen in hyrogen enriched condition. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Diesel engine; Smoke; NOx; Rate of heat release; SPARK-IGNITION ENGINE; INTERNAL-COMBUSTION ENGINE; PORT FUEL-INJECTION; NITROGEN ADDITION; GASOLINE-ENGINE; NOX FORMATION; CNG ENGINE; GAS; PARAMETERS; MIXTURES; Chemistry; Electrochemistry; Energy & Fuels